2013
DOI: 10.5751/es-05319-180212
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon among the Commons? Disentangling the Sustainability of the Peruvian Anchovy Fishery

Abstract: ABSTRACT. The term "commons" refers to collectively exploited resources and their systems of usage; a synonymous term is common pool resources. Fisheries are typical common pool resources and also one of the most conspicuous examples of unsustainable use of natural resources. We examine one of the few globally important fisheries that is held to be sustainable, the Peruvian anchovy fishery, and considers the extent to which the institutional characteristics of the fishery conform to design principles that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…A single analysis of the principles would only give a snapshot. Therefore, principles should be analyzed over time, and the principles should be made or treated as dynamic, in the manner of Gelcich et al (2006); Yandle (2008) and Arias Schreiber and Halliday (2013), who analyzed the principles at two time periods. In our case studies, we attempted to do this by analyzing trends in social-ecological change when assessing the principles, and by illustrating the importance of changes by pointing out that the formation of the POPA group and its participatory research initiative (Trimble and Berkes 2013) made a difference in meeting at least two design principles.…”
Section: Challenges For the Transition Towards Adaptive Co-managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A single analysis of the principles would only give a snapshot. Therefore, principles should be analyzed over time, and the principles should be made or treated as dynamic, in the manner of Gelcich et al (2006); Yandle (2008) and Arias Schreiber and Halliday (2013), who analyzed the principles at two time periods. In our case studies, we attempted to do this by analyzing trends in social-ecological change when assessing the principles, and by illustrating the importance of changes by pointing out that the formation of the POPA group and its participatory research initiative (Trimble and Berkes 2013) made a difference in meeting at least two design principles.…”
Section: Challenges For the Transition Towards Adaptive Co-managementmentioning
confidence: 99%
“…Ostrom's (1990) eight design principles are remarkable in the scholarly literature about commons sustainability and collective action because they capture some of the commonalities regarding the necessary conditions. These principles have been used to evaluate and diagnose various resource systems, including fisheries (e.g., Pinkerton and Weinstein 1995;Gelcich et al 2006;Yandle 2008;Arias Schreiber and Halliday 2013;McClanahan et al 2013;Fleischman et al 2014;Galappaththi and Berkes 2015), and some are among the necessary conditions for co-management and adaptive co-management (e.g., Pomeroy 2007; Armitage et al 2009). Cox et al (2010) analyzed 91 of these studies and concluded that Ostrom's eight principles were well supported empirically, but suggested splitting three of them, in line with the evidence from the cases.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Ostrom argues that a self-governed CPR is one wherein 'major appropriators of the resource, are involved over time in making and adapting rules within collectivechoice arenas' and in our modern political economies it is highly usual that 'in a self-governed system, participants make many, but not necessarily all, rules that The Daudkandi model of community floodplain aquaculture in Bangladesh 857 affect the sustainability of the resource system and its use' (Ostrom 2002(Ostrom , 1317. Initially in the co-management era, primary partners in managing a resource were government and the users, and that regime has been looked into through Ostrom's framework (Yandle 2003(Yandle , 2008Gelcich et al 2006;Schreiber and Halliday 2013;McClanahan et al 2015). That clear dichotomy has changed in subsequent years through various experimentations, and in the case of present study, as will be shown, community users formed the main partnership with the NGO without any government initiative framework for and involvement in managing their resource.…”
Section: Introductionmentioning
confidence: 85%
“…However, the fulfilment of all these principles -about which none of the users had any previous idea-in field level is an extremely complex ongoing process. The sustainability of a CPR solely in terms of compliance with Ostrom's principles cannot be predicted as there is strong possibility of the presence of external factors like market demands or resource's various properties (Cox et al 2010;Schreiber and Halliday 2013). Cox et al (2010) also mentioned the limitations of Ostrom's principles in considering user community's internal power play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation